2020
DOI: 10.1111/sed.12743
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing the product of concave‐bank sedimentary processes in fluvial meander‐belt strata

Abstract: Downstream migration of point bars is an important process in meander belts. Inherent to downstream migration is sediment accumulation in concave channel banks, immediately adjacent to and downstream of convex point bars. Despite this, associated concave bank processes are often overlooked, with depositional products sparsely identified in the stratigraphic record. Counter‐point‐bar deposits are a type of concave‐bank deposit that have been positively identified in subsurface three‐dimensional seismic datasets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Many depositional concave banks are associated with a zone of flow separation along the river bank (Hickin, 1978;Makaske and Weerts, 2005;Blanckaert et al, 2013;Ghinassi et al, 2018). Few studies of modern and ancient meander belt deposits have identified counter point bar deposits, likely due to the qualitative and limited recognition criteria (Durkin et al, 2020). Although the number of well-documented field examples is limited, the existing data suggest that counter point bars are generally finer grained than adjacent point bars and can be dominated by siltand mud-grade sediment (Hickin, 1979;Page and Nanson, 1982;Makaske and Weerts, 2005;Smith et al, 2009Smith et al, , 2011Hooke and Yorke, 2011;Hubbard et al, 2011;Durkin et al, 2017Durkin et al, , 2018Durkin et al, , 2020Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Many depositional concave banks are associated with a zone of flow separation along the river bank (Hickin, 1978;Makaske and Weerts, 2005;Blanckaert et al, 2013;Ghinassi et al, 2018). Few studies of modern and ancient meander belt deposits have identified counter point bar deposits, likely due to the qualitative and limited recognition criteria (Durkin et al, 2020). Although the number of well-documented field examples is limited, the existing data suggest that counter point bars are generally finer grained than adjacent point bars and can be dominated by siltand mud-grade sediment (Hickin, 1979;Page and Nanson, 1982;Makaske and Weerts, 2005;Smith et al, 2009Smith et al, , 2011Hooke and Yorke, 2011;Hubbard et al, 2011;Durkin et al, 2017Durkin et al, , 2018Durkin et al, , 2020Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of flow divergence in modern rivers also suggests that sedimentary successions accreted by stacking of bank-attached bar bodies (for example, point bars) would be exclusively dominated by nearly orthogonal divergence angles. This inference is corroborated in sites where ancient point-bar bodies are unambiguously shown by 3D seismic data (Durkin et al, 2017), extensive three-dimensional outcrops (Durkin et al, 2020) or planform exposures (Ielpi & Ghinassi, 2014;Wu et al, 2015;Simon & Gibling, 2017). These cases document nearly orthogonal divergence angles, with few values exceeding 140°in association with ripple crosslamination developed in the uppermost bar zone or in association with counter-point bars (Ghinassi & Ielpi, 2015;Simon & Gibling, 2017), where secondary and recirculation currents develop, respectively.…”
Section: Role Of Discharge Variabilitymentioning
confidence: 80%
“…Advances in UAV‐based remote sensing provide an opportunity to reveal outcrop details within this observational gap that have been difficult or impossible to capture with established techniques. Utilising UAV‐SfM has demonstrated effectiveness in supplementing field data with additional perspectives (Chesley & Leier, 2018; Chesley et al, 2017; Durkin et al, 2020; Nesbit et al, 2018; Nieminski & Graham, 2017). This study further demonstrates that UAV‐SfM can be used to identify previously unobserved intermediate‐scale features and link fine‐scale observations with quantifiable geometric and architectural measurements over wide spatial extents (Figure 10A, red dashed box).…”
Section: Discussionmentioning
confidence: 99%